The Use of Digital Technology in Indonesian Language Learning in Elementary Schools: A Systematic Literature Review - Pebriana, Putri Hana; Sari, Cindy Fatika; Anggraini, Nadia Fahira; Pohan, Ratih Nurjannah; Afifah, Rifdah; Febriani, Amelia; Fitrah, Dinia Ahira; Annisa, Nur (The Future of Education Journal, 2026)
This study was conducted to investigate the use of digital technology-based learning media in teaching Indonesian language in elementary schools using a Systematic Literature Review (SLR) approach. The research methodology involves analyzing scholarly articles from both domestic and international sources published in the past 5–10 years and retrieved from indexed databases. The review process includes identification, selection, evaluation, and analysis of articles based on predetermined inclusion and exclusion criteria. The findings show that digital technology-based learning media, such as interactive multimedia, educational videos, learning applications, and online learning platforms, have a positive impact on enhancing students' motivation, understanding of the material, and language skills in elementary schools. Additionally, the use of digital media can create more engaging, relevant, and student-centered learning experiences. However, several challenges exist, including limited facilities, low digital skills among teachers, and unequal access to technology. Therefore, policy support, continuous teacher training, and adequate infrastructure provision are necessary to maximize the use of digital technology-based learning media in Indonesian language education in elementary schools.